2010
DOI: 10.1021/la904447c
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cell Adhesive Behaviors on Superhydrophobic, Superhydrophilic, and Micropatterned Superhydrophobic/Superhydrophilic Surfaces to Their Surface Chemistry

Abstract: A micropatterned superhydrophobic/superhydrophilic surface was successfully fabricated by plasma CVD and VUV irradiation. Physicochemical properties of the superhydrophobic, superhydrophilic, and superhydrophobic/superhydrophilic surfaces were investigated. The roughness structures on the superhydrophilic surface remained intact compared to those of the superhydrophobic surface. The micropatterned superhydrophobic/superhydrophilic surface was used as a scaffold of cell culture. On the micropatterned surface, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
211
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(218 citation statements)
references
References 54 publications
6
211
0
1
Order By: Relevance
“…It has been reported that there is a preferential cell attachment on surfaces with moderate wettability, which permits the adsorption of serum proteins with labile and reversible bonds. The moderate degree of wettability allows cells to deposit their own adhesion proteins, exchanging them with the more rapidly adsorbed serum proteins [28,40,51]. This mechanism was found to be slower on extremely hydrophobic or hydrophilic surfaces; adsorbed proteins showed altered conformation of the domains involved in cell adhesion [42], that resulting in a lack of mature focal adhesion formation, thus justifying the fact that cells do not adhere and proliferate so well on such surfaces.…”
Section: Cell Viability Adhesion and Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that there is a preferential cell attachment on surfaces with moderate wettability, which permits the adsorption of serum proteins with labile and reversible bonds. The moderate degree of wettability allows cells to deposit their own adhesion proteins, exchanging them with the more rapidly adsorbed serum proteins [28,40,51]. This mechanism was found to be slower on extremely hydrophobic or hydrophilic surfaces; adsorbed proteins showed altered conformation of the domains involved in cell adhesion [42], that resulting in a lack of mature focal adhesion formation, thus justifying the fact that cells do not adhere and proliferate so well on such surfaces.…”
Section: Cell Viability Adhesion and Proliferationmentioning
confidence: 99%
“…Anti-bioadhesion applications, aimed at preventing protein adsorption and cell adhesion have been mostly studied in blood compatible materials [21,22]. Nonetheless, few works are found in literature reporting the use of superhydrophobic surfaces as support for cell response studies [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…While most literature suggests that protein adsorption tends to occur more favourably on hydrophobic surfaces or on surfaces with an intermediate wettability (60-90°), other investigations have demonstrated more favourable protein adsorption on hydrophilic surfaces [16]. This conflicting data with regard to the influence of surface wetting on protein adsorption is considered to be the result of the variety of factors which influence protein adsorption, including surface charge, roughness, environmental pH, etc.…”
Section: Introductionmentioning
confidence: 98%
“…Cell adhesion is depended by surface hydrophilicity, surface charge density, surface morphology, specific chemical groups present on the surface of the scaffold [3]. Nanolayers surface properties regulate cell growth, migration, differentiation, synthesis of the extracellular matrix components [7,14].…”
mentioning
confidence: 99%